Estimación volumétrica y del carbono de la biomasa aérea de la cobertura forestal del sector tres de la finca experimental La Represa, propiedad de la Universidad Técnica Estatal de Quevedo - Triviño Jimenez, Wagner Sebastián (2021)
The purpose of this research is to make known the need to carry out studies on the content of biomass, carbon and floristic diversity, to implement new ways of managing planted forests with incentives for conservation as products of the ecosystem services that planted forests provide.The objective of this research is to estimate the volumetric and carbon content of the aerial biomass of the forest cover of sector three of the experimental farm "La Represa" owned by the State Technical University of Quevedo, belonging to the San Carlos parish, Quevedo , Los Ríos province. Within a range of 19.91 ha, by implementing the forest census methodology, 9 families, 16 genera, 16 species and 2,398 tree individuals (≥ 10 cm) were identified; highlighting as the most representative species Teak (Tectona grandis L.F.) with 1,779 individuals. A cubic volume of 1,234.66 m3 was recorded, the species that presented the highest volume were Teak (Tectona grandis L.F.) with 635.67 m3 and Pachaco (Schizolobium parahyba (Vell.) S. F. Blake) with 380.89 m3. By means of the non destructive method, an area biomass of 19.91 Tn / haB and 541.17 Tn / totalB was quantified, which store a carbon content of 13.59 Tn / haC and 270.58 Tn / totalC, the species that presented a greater amount of stored carbon were Pachaco (Schizolobium parahyba (Vell.) with 48.65 Tn / C, Laurel (Cordia alliadora) with 38.29 Tn / C and Fernán Sánchez (Triplaris cumingiana Fisch. y CAMey) with 30 , 54 Tn / C. Keywords: carbon, forest census, forest species, tons